Measurement of the pp(-)-> W gamma plus X cross section at root s=1.96 TeV and WW gamma anomalous coupling limits - Abazov, V. M.; Abbott, B.; Abolins, M.; Acharya, B. S.; Adams, M.; Adams, T.; Agelou, M.; Agram, J. L.; Ahn, S. H.; Ahsan, M.; Alexeev, G. D.; Alkhazov, G.; et al. (American Physical Soc, 2005)
The WW gamma triple gauge boson coupling parameters are studied using p (p) over bar -> l nu gamma + X(l = e, mu) events at root s = 1.96 TeV. The data were collected with the D0 detector from an integrated luminosity of 162 pb(-1) delivered by the Fermilab Tevatron Collider. The cross section times branching fraction for p (p) over bar -> W(gamma) + X -> l nu gamma + X with E-T(gamma) > 8 GeV and Delta R-l gamma > 0.7 is 14.8 +/- 1.6(stat) +/- 1.0(syst) +/- 1.0(lum) pb. The one-dimensional 95% confidence level limits on anomalous couplings are -0.88 < Delta kappa(gamma) < 0.96 and -0.20 < lambda(gamma) < 0.20.